THE ROLE OF PHARMACOECONOMICS IN DETERMINING TREATMENT SELECTION IN INDONESIA: A SCOPING REVIEW - Adinda Amalia; I Kadek Suardiana (Journal Pharmaceutical Science and Application, 2025)
Background: Pharmacoeconomic analysis is a crucial tool for assessing the economic impact of alternative drug therapies, especially amid rising healthcare costs in Indonesia. It evaluates whether the benefits of a treatment justify the additional costs, supporting pharmacists in selecting effective and cost-efficient therapies that enhance patient quality of life. Four main types of pharmacoeconomic studies are commonly used: Cost Effectiveness Analysis (CEA), Cost Minimization Analysis (CMA), Cost Utility Analysis (CUA), and Cost Benefit Analysis (CBA). Objective: This review aims to provide an overview of pharmacoeconomic studies that can serve as a reference for pharmacists in Indonesia in selecting appropriate treatments, focusing on literature from national journals published within the last 10 years. Methods: A literature review was conducted using primary data from national research publications accessed via Google Scholar. Inclusion criteria were studies involving pharmacoeconomic evaluations related to therapy selection, published from 2015 onward in national journals. Studies examined include those covering drug utilization patterns, cost estimation, and alignment with the national formulary. Results: CEA and CUA are the most frequently applied pharmacoeconomic methods in Indonesia, particularly for evaluating antihypertensive, antiinfective, and cardiovascular drugs. These methods offer valuable insights that help pharmacists determine clinically effective and economically viable treatment options. Conclusion: Pharmacoeconomic studies are essential in supporting pharmacists in balancing treatment efficacy with cost considerations. Their application is particularly important in the context of the National Health Insurance (JKN), where informed decisions are needed to ensure cost-effective, sustainable healthcare delivery.   Keywords: Cost Benefit Analysis; Cost Effectiveness Analysis; Cost Minimization Analysis; Cost Utility Analysis; Pharmacoeconomics.